Religion received: A Lutheran consideration of religion. Issue 3 (2nd November 2022) - Kristensen, Johanne S. T.
Abstract: This article considers the conception of religion from a contemporary Lutheran perspective. It begins by recollecting the 20th‐century Protestant strife over the concept of religion, and by articulating a deep Protestant ambivalence in regard to religion. This ambivalence is considered an inherently Lutheran insight essentially belonging to Luther's rediscovering of justification by faith alone, including his simul justus et peccator . Thus, the article asks how this ambivalence might be expressed today in a specifically Lutheran approach to religion. It proposes an answer by reference to a critical phenomenological interpretation of Wolfhart Pannenberg's reception of Luther. This proposal considers the concept of religion as an expression of a genuinely passive and open, historical, and embodied practice, which means that religion is an essentially eschatological concept, and to be conceptualized eschatologically. Such an eschatological approach may serve as both a criticism of current religious practice, and as a promise for a particular human being and the community through, and in which, this particular human lives. Hence, by returning to sola fide, the article proposes to conceptualize religion eschatologically as the received reconciliation and freedom of a Christian.